Kinetika reaksi hidrolisis tepung gaplek dengan katalisator zeolit alam - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Catalytic hydrolysis of dried cassava powder was undertaken in an autoclave provided with rotating machine, heating system and sample device. Experiment was started by feeding 500 ml of water, 15 gram dried cassava powder and 15 gram natural zeolites catalyst into autoclave, set the rotating autoclave speed and temperature at the specified value and then the electric source was switched on. If the specified temperature was attained, samples were taken at 15 minutes intervals to analyse the glucose contents. The conversion increased with reaction time and temperature up to 423K Hydrolysis of dried cassava powder by using natural zeolites as catalyst was pseudo first order with respect to starch concentration. Based on the variables investigated, it was found that the chemical reaction was controlling step. The relation between reaction rate constant and temperature accorded with Arrhenius form and can be expressed as, kR= 2,324 10" exp (-26,131.74/R7) with an average error 1.42%.